THE PORTRAYAL OF CPEC IN RESHAPING PAKISTAN’S REGIONAL GEOPOLITICS AND ECONOMY (Contemporary Journal of Social Science Review, 2025)
This qualitative study explores the transformative role of the China-Pakistan Economic Corridor (CPEC) in reshaping Pakistan’s regional geopolitics and economic landscape. CPEC, a flagship component of China’s Belt and Road Initiative (BRI), is often portrayed as a catalyst for economic revitalization, regional integration, and strategic realignment. Through in-depth interviews with policy experts, government officials, and academics, combined with thematic analysis of policy documents, speeches, and media discourse, this study investigates how CPEC is perceived to influence Pakistan’s diplomatic posture, economic sovereignty, and regional alliances. The findings reveal that CPEC is redefining Pakistan's geostrategic importance, enhancing connectivity with China and Central Asia while simultaneously triggering complex geopolitical responses from neighboring countries, particularly India and the United States. Economically, participants highlight both opportunities such as infrastructure development, trade corridors, and foreign investment and concerns, including debt dependency, uneven provincial benefits, and transparency in governance. This research underscores the dual nature of CPEC as a strategic opportunity and a source of emerging vulnerabilities. The study contributes to a deeper understanding of the intersection between development projects and geopolitical agency in the Global South, offering policy recommendations to ensure equitable growth and regional stability through CPEC.